1995
DOI: 10.1046/j.1471-4159.1995.65041636.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Agonist‐Specific Intracellular Trafficking of an Epitope‐Tagged μ‐Opioid Receptor Expressed in HEK 293 Cells

Abstract: We expressed the cloned μ‐opioid receptor (μR) in high abundance (5.5 × 106 sites/cell) with an amino‐terminal epitope tag (EYMPME) in human embryonic kidney 293 cells. The epitope‐tagged receptor (EE‐μR) was similar to the untagged μR in ligand binding and agonist‐dependent inhibition of cyclic AMP accumulation. By confocal microscopy, the labeled receptor was shown to be largely confined to the plasma membrane. Pretreatment with morphine failed to affect the cellular distribution of the receptor as judged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(156 citation statements)
references
References 23 publications
13
143
0
Order By: Relevance
“…In particular, our results suggest that the distal portion of the carboxyl-terminal cytoplasmic domain of DOR is not required for regulated endocytosis but functions as an endocytic brake that is "released" by phosphorylation in order to allow endocytosis of full-length receptors to occur. At first glance, this hypothesis is reminiscent of a previous study suggesting that the cytoplasmic tail of the -opioid receptor inhibits endocytosis (29). However, in this case, truncation of the corresponding tail domain caused constitutive endocytosis of receptors (i.e.…”
Section: Discussionmentioning
confidence: 73%
“…In particular, our results suggest that the distal portion of the carboxyl-terminal cytoplasmic domain of DOR is not required for regulated endocytosis but functions as an endocytic brake that is "released" by phosphorylation in order to allow endocytosis of full-length receptors to occur. At first glance, this hypothesis is reminiscent of a previous study suggesting that the cytoplasmic tail of the -opioid receptor inhibits endocytosis (29). However, in this case, truncation of the corresponding tail domain caused constitutive endocytosis of receptors (i.e.…”
Section: Discussionmentioning
confidence: 73%
“…In HEK293 cells, phosphorylation of the p-opioid receptor was increased only 80% above control (Arden et al, 1995). Furthermore, the hippocampal slice has a heterogeneous population of neurons, not all of which necessarily have averages of the control values for that experiment.…”
Section: Figmentioning
confidence: 95%
“…17 in the case of the µ-opioid receptor, we and others have reported that compounds can display clearly different profiles in G-protein activation and β-arrestin recruitment, with morphine exhibiting low emax values in β-arrestin recruitment/receptor internalization but high emax values in assays measuring G-protein activation. [18][19][20][21] However, emax values are not always a good indicator of efficacy. Herein, we have shown that some ligands do show agonist-directed conformational states; for instance, morphine does not differentiate from the other ligands in terms of efficacy (tau) for G-protein activation but does differentiate in terms of efficacy (emax) in the β-arrestin assay.…”
Section: Drugs and Chemicals Usedmentioning
confidence: 99%